Analisis Kinerja Struktur Gedung Rusun TNI AU Halim Perdanakusuma Dengan Menggunakan Metode Pushover Analysis - Prima, Yonas; Lydia Darmiyanti (Jurnal Sipil Krisna, 2023)
At this time, planning for earthquake-resistant multi-storey buildings in Indonesia is important because Indonesia is in a very active tectonic zone, a position caused by the meeting of the 3 large plates and 9 small plates of the world & forming complex plates meeting paths, this makes Indonesia a countries vulnerable to earthquakes. One method of analytical approach for the performance of earthquake-resistant reinforced concrete structures is push load analysis which is used to reveal the performance of building structures during an earthquake by presenting them using performance levels according to regulations, so this planning is usually called performance-based earthquake resistant planning. The performance level will indicate the collapse behavior of the building during an earthquake according to existing conditions. Pushover analysis & performance evaluation on vertical and horizontal elements is assisted by ETABS software. The results of the pushover analysis show that the performance point of the rusun TNI AU Halim Perdanakusuma building for loading in the X-direction is 440.471 mm with a shear force of 38363.2261 kN, while for the Y-direction the performance point obtained is 457.276 mm with a shear force of 55150.5802 kN. From the performance point, the structural drift resulting from loading in the X-direction and Y-direction is 0.824% & 0.855%, so the structure's performance level is based on the drift limits required by FEMA 356 and ATC-40 including the direct occupancy level. Based on the capacity curve, the maximum base shear force obtained is 46734.5513 kN & the resulting displacement in the X- direction is 710.310 mm & while in the Y-direction, the maximum base shear force obtained is 76055.6401 kN & the resulting displacement is 904.504 mm.